Dacryocystorhinostomy ostium: parameters to evaluate and DCR ostium scoring - Ali MJ (Dove Medical Press, 2014)
Mohammad Javed Ali,1 Alkis James Psaltis,2 Peter John Wormald2 1Dacryology Service, L V Prasad Eye Institute, Hyderabad, Telangana, India; 2Department of Surgery–Otorhinolaryngology, Head and Neck Surgery, The University of Adelaide, Adelaide, SA, Australia Aim: This study aims to provide a systematic protocol for the evaluation of a dacryocystorhinostomy (DCR) ostium and to propose a scoring system to standardize the assessment.Methods: Retrospective evaluation of 125 consecutive lacrimal ostia post-DCR was performed. Medical records were screened, and photographs and videos were assessed to note the details of various ostial parameters. The major time points in evaluation were 4 weeks, 6 weeks, 3 months, and 6 months post-DCR. The ostia were defined and parameters like shape, size, location, and evolution of ostium were noted. Evaluation parameters were defined for internal common opening (ICO), ostium stents, and ostium granulomas. Ostium cicatrix and synechiae were graded based on their significance. Surgical success rates were computed and ostium characteristics in failed cases were studied.Results: A total of 125 ostia were evaluated on the aforementioned ostium parameters. Because five ostia showed a complete cicatricial closure with no recognizable features, the remaining 120 ostia were studied. The ostium location was anterior to the axilla of middle turbinate in 85.8% (103/120) of the cases. Moreover, 76.6% (92/120) of the ostia were circular to oval in shape, with a shallow base. The ostium size was >8×5 mm in 78.3% (94/120) of the cases. The ICO was found to be located in the central or paracentral basal area in 75.8% (91/120). The anatomical and functional success rates achieved were 96% and 93.6%, respectively. All the five cases with anatomical failures showed a complete cicatrization and the ICO movements were poor in all the three cases of functional failure.Conclusion: The article attempts to standardize the postoperative evaluation of a DCR ostium and provides a systematic protocol and scoring system for possible use by surgeons and researchers alike. Keywords: DCR, ostium, score, lacrimal, nasal endoscopy